Estrutura de capital: um estudo empírico sobre a ocorrência de equity market timing nas decisões de financiamento das companhias abertas listadas na Bolsa de Valores de São Paulo - Vallandro, Luiz Felipe Jostmeier (Universidade do Vale do Rio do Sinos, 2009)
This study examines the implications of the theory of equity market timing on the capital structure in the Brazilian public companies. Equity market timing, or windows of opportunities, can be defined as the right moment to issue equity when the market value is high, relative to book value, indicating that the firm is overvalued and the cost of capital is low. Baker and Wurgler (2002) developed a model to test the equity market timing theory in the American capital market. The results are consistent with the hypothesis that market timing has large and persistent effects on capital structure. Furthermore, they found out that the impacts persist for a decade after the IPO of the firms, proving that companies in United States take advantage of the windows of opportunities to form their capital structures. Assuming the Baker and Wurgler’s propositions, the equity market timing theory was tested in Brazilian capital market for a group of companies that went public between 1997 and 2007. Both market and book lever
Keywords: Alavancagem; Custo de capital; Equity market timing; Oferta pública inicial de ações; Valor de mercado; Estrutura de capital; Cost of capital; Initial public offering; Leverage; Market value; Capital structure; Ciências Sociais Aplicadas